Hard luck: Diary of a wimpy kid - "Kinney, Jeff" (London; Puffin, 2013)
"Greg Heffley's on a losing streak. His best friend, Rowley Jefferson, has ditched him, and finding new friends in middle school is proving to be a tough task. To change his fortunes, Greg decides to take a leap of faith and turn his decisions over to chance. Will a roll of the dice turn things around, or is Greg's life destined to be just another hard-luck story?"-- Provided by publisher
Keywords: English fiction-Diary fiction